Molecular modeling on kappa opioid receptor and its interaction with nonpeptide kappa opioid agonists - Liu Dong-xiang; Jiang Hua-liang; Shen Jing-shan; Zhu Wei-liang; Zhao Lei; Chen Kai-xian; Ji Ru-yun (Acta Pharmacologica Sinica, 2016)
AIM: To study the interaction between kappa-opioid receptor and its nonpeptide agonists. METHODS: The ""conservation patterns"" for G-protein coupled receptors (GPCR) were used to determine 7 transmembrane (TM) regions. Taking the crystallographic coordinates of bacteriorhodopsin (BR) as the template, the 3D structural model was constructed for 7 TM of kappa-opioid subtype with molecular mechanics (MM) method. Five highly active nonpeptide kappa-opioid agonists were docked into the 7 helices of kappa-opioid receptor to study the ligand-receptor interaction. RESULTS: Four important interactions between U-50488-like agonists and kappa-opioid receptors were drawn according to our modeling study: (1) the protonated pyrrolidine nitrogen of the ligands formed a hydrogen-bond with the carboxyl of Asp138; (2) the carbonyl oxygen of ligands forms a hydrogen bond to the hydroxyl of Ser187; (3) the aryl groups connected to acylamide of the agonists inserted into a hydrophobic cavity enclosed by residues Val239, Val236, Phe235, Val232, Leu186, and Trp183; (4) the pyrrolidine of the ligands in the complexes was surrounded by Ile290, Asp138, Ile194, Ile135, and Cys131. CONCLUSION: The proposed interaction mechanism is helpful for further mutant experiments and designing novel potent kappa-opioid agonists.